The El Mozote massacre : human rights and global implications - Binford, Leigh, 1948- (The University of Arizona Press, 2016)
"This book brings a fresh perspective on what may be the largest massacre in modern Latin American history. Many new additions are included, such as data from half a dozen field trips, discussions of reconstruction and the fight for justice, and the relation of the massacre to the region"--Provided by publisher.